Effects of static postural loading on the performance of short-term/working memory tasks. - Son, Minseok; Hyun, Soomin; Baek, Seungwon; Beck, Donghyun; Park, Woojin (Ergonomics, 2026)
This study empirically investigated the effects of static postural loading on the performance of basic short-term/working memory (STM/WM) tasks. Four posture groups varying in the magnitude of postural loading were considered. Each group corresponded to one of the four action categories of the OWAS posture classification scheme and consisted of three postures belonging to the action category. Three STM/WM tasks, the Corsi block-tapping, digit span, and 3-back tasks, were considered to examine the visuo-spatial sketchpad, phonological loop, and central executive sub-systems of WM. Thirty participants conducted the STM/WM tasks while statically holding each of the twelve postures. Friedman test results revealed that postural loading significantly affected the STM/WM task performance for each of the three experimental tasks (p <.001). The current study findings may help understand the impacts of postural loading on the worker's concurrent cognitive task performance in various physical-cognitive dual task situations. Practitioner Summary: This study empirically investigated the effects of postural loading on the performance of three basic STM/WM tasks during static posture holding. An increase in postural loading decreased all three STM/WM task scores. The study findings may help design various work tasks that require simultaneously conducting physical (postural) and cognitive sub-tasks.